2019
DOI: 10.1016/j.actbio.2019.07.008
|View full text |Cite
|
Sign up to set email alerts
|

Guiding mesenchymal stem cell differentiation using mesoporous silica nanoparticle-based films

Abstract: People interested in the research are advised to contact the author for the final version of the publication, or visit the DOI to the publisher's website. • The final author version and the galley proof are versions of the publication after peer review. • The final published version features the final layout of the paper including the volume, issue and page numbers. Link to publication General rights Copyright and moral rights for the publications made accessible in the public portal are retained by the author… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 41 publications
1
21
0
Order By: Relevance
“…Of note, the procedure did not alter the chemical properties of the neat and functionalized surfaces; therefore, the NPs deposition differed only for the chemical functionalization. These results agree with the work of Andrée L. and co-authors that used mesoporous NPs with different characteristics to obtain a substrate for evaluating the effect on mesenchymal stem cell differentiation [16]. Hence, our model allows the evaluation of the hBM-MSCs and hASC proliferation, shape, adhesion, and differentiation.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Of note, the procedure did not alter the chemical properties of the neat and functionalized surfaces; therefore, the NPs deposition differed only for the chemical functionalization. These results agree with the work of Andrée L. and co-authors that used mesoporous NPs with different characteristics to obtain a substrate for evaluating the effect on mesenchymal stem cell differentiation [16]. Hence, our model allows the evaluation of the hBM-MSCs and hASC proliferation, shape, adhesion, and differentiation.…”
Section: Discussionsupporting
confidence: 90%
“…In fact, stem cells are able to collect the chemical-physical cues of biomaterials and transduce them in intracellular signaling that may influence the cell shape and function [7,22,35,36,[49][50][51]86]. In this regard, some research groups have demonstrated that mesoporous NPs may influence cell behavior or stem cell differentiation through their nanoscale structure, functionalization, and delivery system [16,22,87,88].…”
Section: Discussionmentioning
confidence: 99%
“…Cells intend to bind at sharp edges of TiO 2 -NTs walls, 48 and the changed cellular morphology usually indicates the direction of cell differentiation. 49 The SEM images (Figure 2A) and phalloidin/DAPI staining ( Figure 2B) showed that macrophages that adhered to various surfaces exhibited different morphology. Macrophages cultured on the surface of Ti and TiO 2 -NTs formed a more rounded shape, which indicated the differentiation of the M1 phenotype.…”
Section: Cell Morphology and Proliferationmentioning
confidence: 98%
“…osteogenic lineage. These films have been loaded with dexamethasone, a glucocorticoid known to induce osteogenic differentiation of MSCs in vitro [126]. Temporally controlled dexamethasone delivery led to increased ALP levels and matrix mineralization compared to directly supplementing dexamethasone to the medium.…”
Section: Addition Of Drugs Relevant For Bone Tissue Homeostasismentioning
confidence: 99%